Finite different method and differential Quadrature method for solving burgers’ equation / Muhammad Afiq Khasim and Abdul Rahim Zulkefli - Khasim, Muhammad Afiq; Zulkefli, Abdul Rahim (2019)
In this study, the Finite Difference Method and Differential Quadrature Method are used to solve the Burgers equation. The different number nodes and different initial condition are used in these methods to investigate in terms of accuracy. The solutions of these methods are compared in terms of accuracy of the numerical solution by using the graph. C++ are used to find numerical solution for those method and the exact solution solve by using maple. For results and tabulate, result are collected to compare the solution in terms of the accuracy of the numerical solution with the exact solution. The different number of nodes and difference initial condition can affect the solution of burgers equation in term of accuracy study. To find the best method to solve this equation, those method compare by using sum of square error, SSE. Decreasing the number of nodes will increasing the errors of the solution. Generally, from the results between Finite Difference Method and Differential Quadrature Method showed the Differential Quadrature Method is better than the Finite Difference Method in terms of accuracy of the numerical solution.